Concurrent information processing and computing - NATO Advanced Research Workshop on Concurrent Information Processing and Computing ( 2003 : Sinaia, Romania); Nicolau, Alexandru; Grigoras, Dan, 1956- (Amsterdam : IOS Press, 2005)
57